Hemolytic Crisis following Naphthalene Mothball Ingestion in a 21-Month-Old Patient with Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency - Maricel Dela Cruz; Muhammad Masood Khalid; Ahmed Mostafa; Muhammed Ershad; David Vearrier; Rita McKeever (Case Reports in Pediatrics)
Introduction. Naphthalene is an aromatic hydrocarbon that may be found in mothballs and deodorizers. Exposure can occur by ingestion or dermal absorption. We present a case of acute hemolysis requiring blood transfusion in a 21-month-old male with a history of glucose-6-phosphate dehydrogenase (G6PD) deficiency after ingestion of a naphthalene-containing mothball. Case Presentation. A 21-month-old male with G6PD deficiency presented to the emergency department three hours following an exploratory ingestion of a naphthalene-containing mothball. On arrival, the patient was tachycardic with normal blood pressure, temperature, respiratory rate, and oxygen saturation. Initial laboratory studies showed significant anemia with elevated reticulocyte count, blood urea nitrogen, total bilirubin, and lactate dehydrogenase. Haptoglobin level was low, and the methemoglobin level was unremarkable. The patient was admitted to the pediatric intensive care unit and underwent blood transfusion. Discussion. This case serves as a reminder that mothballs, a ubiquitous household item, can be hazardous when accessible to vulnerable children. Care should be taken to secure these products and prevent ingestion.